Gradle for Android - Kousen, Kenneth A. (O'Reilly Media, 2015)
"If you're an experienced Android developer or just preparing to jump in, you need to know the Gradle automated build system. In this video workshop, Java consultant Ken Kousen shows you how to work with Gradle when developing apps for Android devices. Built on Ant and Maven concepts, Gradle uses a Groovy-based domain-specific language rather than XML for declaring the project configuration. This video helps Groovy and Java programmers quickly master this Android build tool."--Resource description page.